Penerapan Pendekatan Stem Berbasis LKPD Berbasis PIT Dalam Upaya Meningkatkan Hasil Belajar Ilmu Falak Siswa - Dwi Mulyani, Eva; Pertiwi, Asih; Asnita, Dessy; Rosmiati; Wulandari, Febriantika (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
The aim of this research is to determine the effectiveness of the PIT-based LKPD-assisted STEM approach to improve student abilities and improve student learning outcomes in ilmu falak learning. This type of research is quantitative research using the Quasi Experiment method with a pretest desaign-posttest control design research. The population used in this research were all class XII students at MA Ulumul Quran Langsa. The sampling technique used purposive sampling technique, with class XII IPS as the experimental class and class XII IPA as the control class. The data collection techniques use observation, tests and documentation. The percentage of N-Gain values ​​for the control class was 52% in the less effective category, while in the experimental class it was 60% in the quite effective category. Based on the results of this research data processing, it can be concluded that the application of the STEM approach assisted by PIT-based LKPD is quite effective in improving students' learning outcomes.